Genome-wide identification, expression and salt stress tolerance analysis of the GRAS transcription factor family in Betula platyphylla - He, Zihang; Tian, Zengzhi; Zhang, Qun; Wang, Zhibo; Huang, Ruikun; Xu, Xin; Wang, Yucheng; Ji, Xiaoyu (Frontiers in Plant Science, 2022)
The GRAS gene family is a plant-specific family of transcription factors and play a vital role in many plant growth processes and abiotic stress responses. Nevertheless, the functions of the GRAS gene family in woody plants, especially in Betula platyphylla (birch), are hardly known. In this study, we performed a genome-wide analysis of 40 BpGRAS genes (BpGRASs) and identified typical GRAS domains of most BpGRASs. The BpGRASs were unevenly distributed on 14 chromosomes of birch and the phylogenetic analysis of six species facilitated the clustering of 265 GRAS proteins into 17 subfamilies. We observed that closely related GRAS homologs had similar conserved motifs according to motif analysis. Besides, an analysis of the expression patterns of 26 BpGRASs showed that most BpGRASs were highly expressed in the leaves and responded to salt stress. Six BpGRASs were selected for cis-acting element analysis because of their significant upregulation under salt treatment, indicating that many elements were involved in the response to abiotic stress. This result further confirmed that these BpGRASs might participate in response to abiotic stress. Transiently transfected birch plants with transiently overexpressed 6 BpGRASs and RNAi-silenced 6 BpGRASs were generated for gain- and loss-of-function analysis, respectively. In addition, overexpression of BpGRAS34 showed phenotype resistant to salt stress, decreased the cell death and enhanced the reactive oxygen species (ROS) scavenging capabilities and proline content under salt treatment, consistent with the results in transiently transformed birch plants. This study is a systematic analysis of the GRAS gene family in birch plants, and the results provide insight into the molecular mechanism of the GRAS gene family responding to abiotic stress in birch plants.